Sexual Morbidity Associated With Poorer Psychological Adjustment Among Gynecological Cancer Survivors. Issue 3 (1st April 2010) - Levin, Anna O.; Carpenter, Kristen M.; Fowler, Jeffrey M.; Brothers, Brittany M.; Andersen, Barbara L.; Maxwell, G. Larry
Abstract : Objectives: Sexual morbidity is a distressing and undertreated problem in gynecological cancer survivorship known to occur early and persist well beyond the period of physical recovery. Although often studied as a separate domain, sexuality represents an integral component of psychological adjustment and quality of life (QoL) that is adversely affected by cancer treatments. The present study tests the association between sexual morbidity, and adverse psychological adjustment and QoL outcomes. Methods: A cross-sectional design was used. The participants were gynecological (cervical, endometrial, ovarian, and vulvar) cancer survivors who were partnered (N = 186), whose cancer was diagnosed 2 to 10 years previously, and who were at least 6 months post any cancer therapy. Most had been found to have early-stage disease (70%) and were treated with hysterectomy (77%), chemotherapy (43%), and/or radiotherapy (23%). Sexual morbidity was operationalized as a multidimensional construct including sexual behavior, sexual functioning, and subjective sexual satisfaction, assessed by patient self-report. Outcomes included self-reported depressive symptoms, traumatic stress symptoms, cancer-specific stress, stress about body changes, and QoL. Nurse-rated of performance status and disruptive signs/symptoms of treatment toxicity, as well as relevant sociodemographic and disease variables were collected as potential controls. Results: Hierarchical multiple regression analyses tested sexual morbidity as a predictor of poor outcomes. All statistical models were significant, accounting for 12% to 53% of the variance in psychological adjustment/QoL. Sexual morbidity covaried with worsened depressive symptoms, body change stress, and psychological QoL beyond the negative contributions of (older) age, (poorer) performance status, and (greater) fatigue. Notably, disease and treatment variables were not statistically significant correlates of psychological adjustment or QoL. Conclusions: These findings suggest that prevention or treatment of sexual morbidity might foster improved psychological adjustment/QoL. Given the high rates of sexual morbidity in this population and the connection between sexuality and broader psychological adjustment/QoL, there is a clear need for better integration of sexuality rehabilitation into routine clinical care.